"Muslim Hatuhaha" di Pulau Haruku Maluku Tengah - Yance Zadrak Rumahuru (Masyarakat Indonesia, 2010)
The Moslem community in Haruku Island has been discriminated since the colonial era. Before the Europeans entered the Moluccas Islands, colonizing and Christianizing most negeri in Central Moluccas, the great negeri of Haruku Island in Uli Hatuhaha consisting of Pelauw, Hulaliuw, Rohomoni, Kailolo and Kabauw were Moslem dominated areas. In the colonial era, the Moslem community in central Moluccas did not enjoy the same access and opportunity as the Christian community to education. This affected the economic, political and social life of Moslem communities until the early days of the Indonesian struggle for Independence. Besides discrimination by the Dutch colonizers, the Moslem community in Haruku Island was also subordinated by other groups (Moslems and Christians). This research studies the identity construction and change occurring in the Moslem community in Pelauw, Haruku Island district, Central Maluku regency. This research observes that the Moslem Maluku community in Pelauw negeri has multiple identities. Identity construction and social change have a dynamic that occur concurrently with particular moments in the social life of the people of Moluccas. Another interesting finding is that religion plays an important role in influencing human mentality and human resources in Pelauw. They construct the current identity of the Pelauw people.Keywords: identity, discrimination, social change